Decompression with interbody fusion versus decompression alone for degenerative lumbar diseases: A meta-analysis - Yuxian Chen; Shenglin Lei; Wei Lin; Yilin Huang; Pinying Cheng; Shuling Gu; Dongping Wang (PLoS ONE, 2025)
Objective To appraise the clinical effectiveness and complications of two surgical approaches, namely decompression alone (DA) versus decompression with interbody fusion (DF), in managing degenerative lumbar diseases (DLD). Methods As of July 1, 2024, an exhaustive search identified all randomized controlled studies and cohort studies comparing DA and DF in DLD management. Relevant data were extracted using strict criteria, and study quality was assessed via the Newcastle-Ottawa Scale and Cochrane Collaboration’s tool. The extracted outcomes encompassed a range of measures, including operative duration, intraoperative hemorrhage, hospitalization length, time to ambulation, short form 12 physical component score (SF12-PCS), low back pain visual analog scale (VAS) score, leg pain VAS score, Oswestry disability index (ODI), Japanese orthopedic association (JOA) score, EuroQol five dimensions (EQ-5D), incidence of complications, reoperation rate, and Odom’s criteria. Results A total of 35 articles were included in this study, involving 12,030 patients. Of these, 7,442 patients were in the DA group, while 4,588 were in the DF group. Operative duration was shorter (MD = −89.09, 95%CI −92.71, −85.47, P < 0.00001), intraoperative hemorrhage was less (MD = −242.26, 95%CI −252.16, −232.36, P < 0.00001), hospitalization length was shorter (MD = −2.36, 95%CI −2.59, −2.14, P < 0.00001), and time to ambulation was reduced (MD = −10.49, 95%CI −12.52, −8.46, P < 0.00001) in the DA group than in the DF group. At the final follow-up for ODI, the DF group demonstrated statistically superior outcomes compared to the DA group (MD = 1.28, 95%CI 0.35, 2.21, P = 0.007). Data revealed no significant differences in SF12-PCS, JOA score, back pain VAS score, leg pain VAS score, final follow-up EQ-5D, reoperation rates, complication rates, and Odom’s criteria (P > 0.05). Conclusion When treating DLD, DA offers more favorable outcomes in terms of operative duration, intraoperative hemorrhage, hospitalization length, and time to ambulation. These findings suggest that DA should be considered the preferred surgical approach for most DLD patients, unless specific indications for fusion exist. Clinicians should tailor decisions to each surgery’s specifics to optimize patient outcomes. Trial registration PROSPERO registration number: CRD42024580975.